The effect of providing additional food for students on improving the quality of education in Atuka Village, Mimika District - Simon Roba Patandianan; Risky Novan Ngutra; Hasan Basri Umar (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study aims to analyze the impact of the Supplementary Feeding Program (PMT) on education quality in Kampung Atuka, Mimika Regency, with a focus on academic achievement, attendance rates, and dropout rates. It also considers nutritional status as a mediating factor, and parental support and learning environment as moderating factors. Research Methodology: The study applied a quantitative approach using descriptive statistics, Spearman correlation, and multiple linear regression, supported by mediation and moderation tests. To complement the quantitative data, qualitative analysis was carried out through interviews with students, teachers, and parents, providing contextual insights into the program’s effectiveness. Results: The findings indicate that PMT does not directly and significantly affect academic performance or student attendance but improves nutritional status, which is positively associated with academic achievement. The learning environment and parental support were not found to significantly moderate the relationship between PMT and education quality. Nevertheless, both students and teachers observed benefits such as increased energy and better focus during learning activities. Conclusions: The research concludes that PMT’s role in improving education quality can be optimized when combined with nutritional education programs, active parental involvement, and comprehensive education policies. Limitations: The study is limited by contextual challenges such as household eating patterns and the limited diversity of supplementary food provided, which reduce the overall impact of PMT. Contribution: This study contributes to policy discourse by highlighting the importance of integrating PMT with broader nutritional and educational strategies. It offers practical recommendations for local governments, education offices, and schools to strengthen PMT implementation and achieve greater improvements in education quality in remote regions.